The Antibody Society's antibody validation webinar series - Jan L.A. Voskuil; Anita Bandrowski; C. Glenn Begley; Andrew R.M. Bradbury; Andrew D. Chalmers; Aldrin V. Gomes; Travis Hardcastle; Fridtjof Lund-Johansen; Andreas Plückthun; Giovanna Roncador; Alejandra Solache; Michael J. Taussig; et al. (Taylor & Francis Group, 2020)
In the wake of the reproducibility crisis and numerous discussions on how commercially available antibodies as research tool contribute to it, The Antibody Society developed a series of 10 webinars to address the issues involved. The webinars were delivered by speakers with both academic and commercial backgrounds. This report highlights the problems, and offers solutions to help the scientific community appropriately identify the right antibodies and to validate them for their research and development projects. Despite the various solutions proposed here, they must be applied on a case-by-case basis. Each antibody must be verified based on the content of the product sheet, and subsequently through experimentation to confirm integrity, specificity and selectivity. Verification needs to focus on the precise application and tissue/cell type for which the antibody will be used, and all verification data must be reported openly. The various approaches discussed here all have caveats, so a combination of solutions must be considered.